The leader in me : how schools and parents around the world are inspiring greatness, one child at a time - Covey, Stephen R. (Free Press ; Simon & Schuster, 2008)
An introduction to leadership draws on a program developed for an elementary school to show how to apply the principles of The 7 Habits of Highly Effective People to help everyone, including young children, identify their individual talents and find ways to use them in everyday life.